2017
DOI: 10.1016/j.jaac.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Affect Management for HIV Risk Reduction for Youth in Alternative Schools

Abstract: Objective Adolescents in alternative schools for behavioral and emotional problems have an earlier sexual onset and higher rates of sexual risk than their peers. They also often have difficulty managing strong emotions, which can impair sexual decision-making. Human immunodeficiency virus (HIV) prevention programs for these adolescents may be most effective if skills for coping with strong emotions during sexual situations are included. Method This paper reports the 6-month outcomes of a three-arm randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Finally, IMARA targets individual and social mechanisms shown to affect sexual behavior and these may help explain the reduction in STIs. For example, mental health [ 27 ], greater relationship power [ 28 , 29 ], increased ethnic and gender pride [ 30 ], and stronger emotion regulation [ 31 ] may influence STI outcomes. IMARA promotes mothers as role models for daughters, demonstrating pride in womanhood and Black/African-American identity, cautioning girls about the imbalance of power in age-discrepant relationships, and supporting emotion regulation strategies that improve safe-sex decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, IMARA targets individual and social mechanisms shown to affect sexual behavior and these may help explain the reduction in STIs. For example, mental health [ 27 ], greater relationship power [ 28 , 29 ], increased ethnic and gender pride [ 30 ], and stronger emotion regulation [ 31 ] may influence STI outcomes. IMARA promotes mothers as role models for daughters, demonstrating pride in womanhood and Black/African-American identity, cautioning girls about the imbalance of power in age-discrepant relationships, and supporting emotion regulation strategies that improve safe-sex decisions.…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies have suggested that externalizing symptoms and disorders (e.g., ADHD, conduct disorder) are correlated with greater HIV sexual risk behaviors, including inconsistent condom use and having multiple sexual partners (Brown et al, 2010; Lundberg et al, 2011; Sarver, McCart, Sheidow, & Letourneau, 2014). Although the data have been less consistent, internalizing symptoms and disorders (e.g., depression, anxiety, hopelessness) have also been associated with risk behaviors such as inability to negotiate condom use and decreased assertiveness, but also with later sexual initiation and decreased sexual activity (Caminis, Henrich, Ruchkin, Schwab-Stone, & Martin, 2007; Donenberg & Pao, 2005).…”
mentioning
confidence: 99%
“…It is well known that Black youth in the United States are disproportionately affected by HIV/STIs, yet individual behavior alone cannot fully explain the disparity. In addition to sociostructural conditions known to fuel HIV/STI transmission (e.g., poverty, lack of comprehensive sexual health education), a growing body of research documents the role of factors such as mental illness, psychological distress, and emotion regulation in sexual risk behaviors (Braje, Eddy, & Hall, ; Brawner et al, ; Brown et al, ). In other words, the psychological sequela of mental illnesses like depression and anxiety (e.g., loneliness, impulsivity), the experience of psychological distress in response to internal and/or external conflict, and one's ability to regulate his/her emotions may affect the decisions black youth make about sex and relationships.…”
Section: Introductionmentioning
confidence: 99%
“…We do not know whether these interventions are effective for youth with mental illnesses and/or those who experience psychological symptoms or difficulty with emotion regulation. Comparable interventions specifically designed for youth experiencing mental illnesses and/or psychological symptoms have proven to be effective in decreasing sexual activity and increasing consistent condom use (Brown et al, 2014(Brown et al, , 2017. Yet so few of these interventions exist.…”
mentioning
confidence: 99%